(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Violence is an ubiquitous, changing and polymorphic phenomenon. Its analysis requires a plural methodology, that reflects their peculiarities. The relationship between violence, law and order, with special consideration of the links towards language and tongues are explored.